Personal assistance as a strategic game between state and municipalities in Norway - Jan Andersen (Scandinavian Journal of Disability Research, 2009)
The paper is based on a study of the law-making process of personal assistance in Norway. It discusses some tensions between the state and the municipalities concerning the type and quantity of services with regard to personal assistance. Does introduction of personal assistance imply an extended quantity of services or is it just another way of organising existing services? The signals from the state authorities are ambiguous, and when implementing the reform the municipalities are left to find a solution to this question. This might create a strategic game between the state and the municipalities. It might become an unpredicted side effect of the legislation of personal assistance that the municipalities will become more restrictive in the provision of personal assistance than they were in the experimental period.